ECONOMIC TERMS IN ENGLISH LESSONS IN NON-LINGUISTIC UNIVERSITIES - Shakhida Yusupova; Khayitov Marvarbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article deals with economic terms in English lessons in non-linguistic universities. Therefore, the English language program for non-linguistic universities requires students to have knowledge of English terminology in their specialty and the ability to translate scientific literature rich in terminological vocabulary into their native language.